Improving Learning Outcomes of 2nd Grade Students through Video-Based Learning Media - Nurwulan, Nindy; Nugraha, M. Fahmi; Hendrawan, Budi (Universitas Pendidikan Ganesha, 2020)
The low student learning outcomes due to the lack of learning media make it difficult for students to understand learning material. This study aimed to develop video-based learning media about the properties of objects around us in theme 2, sub-themes 1 grade 2nd. This study used a Research and Development (R&D) type of research with a 4D development model consisting of four stages, namely define, design, develop, and disseminate. The methods used in collecting data were observation, interviews, and questionnaires. Data were analyzed using descriptive statistics. The development of video media is valid with: (a) the results of the reviews by linguists get very good qualifications, (b) the results of the reviews of instructional media experts get very good qualifications, (c) the results of the reviews of subject matter experts get very good qualifications, (d) the results of the trial individuals get very good qualifications, (e) the results of small group trials get very good qualifications, and (e) the results of field trials get very good qualifications. So, this study showed that the validity of video-based learning media on qualifications is very good and can improve student learning outcomes.